2020
DOI: 10.1029/2020wr027199
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Water and Sediment Partitioning in a Delta Channel Network Under Varying Discharge Conditions

Abstract: Channel bifurcations control the distribution of water and sediment in deltas, and the routing of these materials facilitates land building in coastal regions. Yet few practical methods exist to provide accurate predictions of flow partitioning at multiple bifurcations within a distributary channel network. Herein, multiple nodal relations that predict flow partitioning at individual bifurcations, utilizing various hydraulic and channel planform parameters, are tested against field data collected from the Sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 74 publications
3
45
0
Order By: Relevance
“…This is consistent with observations of deltas that evolve over longer timescales than the Huanghe: the Mississippi River delta system experiences major lobe abandonment over centuries to millennia, and its bayou network is an example of a persistent connection between the main and abandoned channels (e.g., bayous LaFourche, Maringuoin, and Teche; Roberts, 1997). Similar examples exist for other river delta systems covering a range of sizes (e.g., Brazos River delta, Taha & Anderson, 2007; Selenga River delta, Dong et al., 2020). Even in lowland river systems, tie channels maintain a persistent freshwater connection to abandoned channels (Day et al., 2008; Rowland et al., 2009, 2005).…”
Section: Discussionsupporting
confidence: 55%
“…This is consistent with observations of deltas that evolve over longer timescales than the Huanghe: the Mississippi River delta system experiences major lobe abandonment over centuries to millennia, and its bayou network is an example of a persistent connection between the main and abandoned channels (e.g., bayous LaFourche, Maringuoin, and Teche; Roberts, 1997). Similar examples exist for other river delta systems covering a range of sizes (e.g., Brazos River delta, Taha & Anderson, 2007; Selenga River delta, Dong et al., 2020). Even in lowland river systems, tie channels maintain a persistent freshwater connection to abandoned channels (Day et al., 2008; Rowland et al., 2009, 2005).…”
Section: Discussionsupporting
confidence: 55%
“…2). Work in other systems has shown that network structure can also be used to estimate flux partitioning and the delivery of fluxes at the shore (Tejedor et al, 2015) and that estimation of nutrient and sediment fluxes can be addressed in similar ways (Dong et al, 2020;Knights et al, 2020).…”
Section: Accepted Articlementioning
confidence: 99%
“…In Section 2.2, we have seen that in the case of a single bifurcation tides exert a stabilizing effect that prevents the closure of one of the two branches in the long-term. However, deltaic networks are formed by several interconnected bifurcations that can interact with each other [58,59,60,61,16].…”
Section: A Simple Model For the Equilibrium Of Tide-influenced Delta Networkmentioning
confidence: 99%